PENERAPAN PROJECT BASED LEARNING DALAM MEMBANGUN PEMAHAMAN KONSEP BELAJAR SISWA PADA MATERI BANGUN RUANG KUBUS DAN BALOK - Siregar, Budi Halomoan; Panjaitan, Chesia Aprina; Anggelina, Maya; Sihombing, Kesia; Simanullang, Asria Ronauli (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Students’ understanding of cube and cuboid concepts has not yet been optimally achieved, as the learning process tends to be teacher-centered and does not sufficiently involve students actively. This condition indicates the need for a learning model that not only actively engages students but also provides meaningful learning experiences. This study was conducted to examine the implementation of the Project-Based Learning (PjBL) model in supporting the conceptual understanding of Grade VIII students at SMP Negeri 34 Medan on the topic of cubes and cuboids. The research employed a qualitative descriptive approach, with the research subjects consisting of 26 Grade VIII students and one mathematics teacher. Data collection techniques included observation, interviews, documentation, and analysis of lesson plan (RPP) documents. Data analysis was carried out qualitatively through the stages of data reduction, data presentation, and conclusion drawing. Based on the research findings, the implementation of the Project-Based Learning (PjBL) model was proven to help students improve their conceptual understanding. This was indicated by students’ ability to explain concepts in their own words, relate concepts to real-life situations, and correctly apply surface area and volume concepts. Therefore, Project-Based Learning can be considered an alternative mathematics learning model that is active, contextual, and student-centered.